2000
DOI: 10.1046/j.1440-1754.2000.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hypoglycaemia in infants of diabetic mothers

Abstract: In well-controlled diabetic mothers, the incidence of early hypoglycaemia in infants is still high, particularly in those mothers who had a longer duration of diabetes. Cord blood glucose level did not identify the infants with hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 17 publications
5
41
0
2
Order By: Relevance
“…The high incidence of hypoglycemia (as defined here) in the present study correlates with a previous report [9] , although in the current study a different cut-off point was used. Other authors who used lower cut-off points described lower rates of hypoglycemia in IDM infants [4,21] .…”
Section: Discussionsupporting
confidence: 89%
“…The high incidence of hypoglycemia (as defined here) in the present study correlates with a previous report [9] , although in the current study a different cut-off point was used. Other authors who used lower cut-off points described lower rates of hypoglycemia in IDM infants [4,21] .…”
Section: Discussionsupporting
confidence: 89%
“…No studies have demonstrated harm from a few hours of asymptomatic hypoglycemia during this normal postnatal period of establishing "physiologic glucose homeostasis." 9 Infants born to mothers with diabetes may develop asymptomatic NH as early as 1 hour after birth 18 and usually by 12 hours of age. 18 In contrast, infants who are large for gestational age or small for gestational age may develop low plasma glucose concentrations at as early as 3 hours of age, 19 and these infants may be at risk of NH for up to 10 days after birth.…”
Section: Figurementioning
confidence: 99%
“…9 Infants born to mothers with diabetes may develop asymptomatic NH as early as 1 hour after birth 18 and usually by 12 hours of age. 18 In contrast, infants who are large for gestational age or small for gestational age may develop low plasma glucose concentrations at as early as 3 hours of age, 19 and these infants may be at risk of NH for up to 10 days after birth. 20 Therefore, at-risk infants should be screened for NH with a frequency and duration related to risk factors specific to the individual infant.…”
Section: Figurementioning
confidence: 99%
“…Previously maintained by a maternal-fetal flux of substrates, neonatal glucose levels fall during the first hour or two after birth, reaching a natural trough before rising to stable neonatal levels. The (27). Holtrop (22) found that the average times for finding low glucose levels in LGA and SGA infants were 2.9 h (range 0.8 h to 8.5 h) and 6.1 h (range 0.8 h to 34.2 h), respectively.…”
Section: When Should At-risk Infantsmentioning
confidence: 99%